Pemikiran Abu Yusuf Tentang Pajak Dan Relevansinya Dengan Kebijakan Ekonomi Di Indonesia - Ach Bakir; Mustofa Mustofa (ITB AAS INDONESIA Surakarta, 2023)
Happiness for all Indonesian people seems to have not been realized until now. This phenomenon is certainly a bad image for the country. Policies must provide solutions that can support, advance, and create prosperity for the state and its citizens. Islam has helped overcome these problems through thinkers who can find solutions to the country's economic problems, including Abu Yusuf. In this study, researchers used qualitative research methods with descriptive analysis based on a literature review. Below are some of Abu Yusuf's views on finance. 1) Provision of public facilities by the state. 2) Unproductive land use. 3) Facilitate economic conditions. 4) State management and utilization of natural resources. 5) Application of the Mukasama system. 6) Distribution and transparency of government revenues. 7) Price; 8) Repeal of Jizyah. Abu Yusuf's economic thinking is relevant to the economic policies implemented in Indonesia, and Abu Yusuf's economic thinking on taxation (al-kharaj) is still relevant to be applied to Indonesia's modern economic system.